A propósito del caminante - Quispe Arroyo, Adolfo (2021)
Puriq (walker) promotes critical reflection on various humanities scientific studies. Along the way or in the dynamics of knowledge, the product of research is embedded from different paradigms and approaches to pedagogical, ethical, political issues, among others. Walking implies dynamics, movement as an engine of history and development in general with a projection to the future, after analyzing the present. Caminante is the Spanish translation of puriq from Quechua roots from this part of Peru (Ayacucho).